Application of the Rapid Application Development Model to a Web-Based Library Information System - Handayani, Rani irma; Astuti, Dyah Ayu (SAN Scientific, 2023)
This study aims to overcome several problems in library management at SMA Negeri 7 Tambun Selatan by designing and developing a web-based library information system using the Rapid Application Development (RAD) method. The background of the problem includes the use of information technology, which is still limited in the library, so the process of recording, borrowing, and returning books is still done manually and takes a long time. In addition, the lack of an effective book search system is also an obstacle to using library collections. This research identifies these problems and formulates aims and objectives to create the right solution. In order to achieve this goal, the research method used involved data collection techniques, such as direct observation in the library, interviews with librarians, and a literature study to obtain relevant information. The result of this research is a web-based library information system that includes managing data on borrowing and returning books, book data, book category data, fines data, and making library data reports. This system allows librarians to record borrowing and returning books more efficiently, as well as facilitate students and staff in finding the desired book quickly and accurately through the search feature provided.